No evidence that economic inequality moderates the effect of income on generosity - Stefan Christian Schmukle; Martin Korndörfer; Boris Egloff (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
A landmark study published in PNAS (Côté S, House J, Willer R, 2015, 112:15838-15843, doi:10.1073/pnas.1511536112) showed that higher income individuals are less generous than poorer individuals only if they reside in a U.S. state with comparatively large economic inequality. This finding might serve to reconcile inconsistent findings on the effect of social class on generosity by highlighting the moderating role of economic inequality. On the basis of the importance of replicating a major finding before readily accepting it as evidence, we analyzed the effect of the interaction between income and inequality on generosity in three large representative data sets. We analyzed the donating behavior of 27,714 U.S. households (Study 1), the generosity of 1,334 German individuals in an economic game (Study 2), and volunteering to participate in charitable activities in 30,985 participants from 30 countries (Study 3). We found no evidence for the postulated moderation effect in any study. This result is especially remarkable because (a) our samples were very large, leading to high power to detect effects that exist, and (b) the cross-country analysis employed in Study 3 led to much greater variability in economic inequality. These findings indicate that the moderation effect might be rather specific and cannot be easily generalized. Consequently, economic inequality might not be a plausible explanation for the heterogeneous results on the effect of social class on prosociality.
Keywords: 330; social class; income; economic inequality; prosocial behavior; generosity